Life cycle sustainability assessment of decentralised com- posting of bio-waste: A case study of the Łódź agglomeration (Poland) - Rybaczewska-Błażejowska, Magdalena; Mazurek, Damian; Mazur, Marcin (Quaestiones Geographicae, 2022)
The study examines the concept of decentralised composting of bio-waste as an alternative approach to current waste management practices, using the Łódź Agglomeration (Poland) as an exemplary case study. Consequently, the aim of the presented research is to compare and discuss the sustainability of the functioning biowaste management system (status quo) against an alternative solution based on decentralised composting. Combined application of process-based life cycle assessment (LCA) and life cycle cost analysis (LCCA) was selected as the methodology to compare the sustainability framework for the waste management practices under analysis. The study has made it clear that decentralised composting of bio-waste offers broader environmental, economic and social benefits, albeit with the level of that benefit being very much correlated with the type of local government area (commune or in Polish gmina). Regardless of the impact category, rural and urban–rural gminas achieved the greatest savings, reaching >90%, and thus are seen to offer the greatest potential for decentralised composting to be put into effect, on the basis of household/backyard composting. In consequence, decentralised composting can constitute a fundamental form of bio-waste management in 20 out of the 28 gminas of the Łódź Agglomeration. The results obtained from the research facilitate the implementation and wider utilisation of decentralised composting, as an important element of the transition to a circular economy, where bio-waste is concerned.